Contributions of paleoecology to Easter Island's prehistory: A thorough review. (15th January 2021) - Rull, Valentí
Abstract: Easter Island (Rapa Nui) is well known for the enigmas surrounding its unique megalithic statues, the moai, and the prehistoric (i.e., pre-European contact) Rapanui society that built them. These enigmas include, among others, the time of the island's settlement, the geographical origin of the first settlers, the technology associated with moai transportation and emplacement, the occurrence (or not) of an ecological and cultural collapse linked to the island's deforestation, and the potential influence of climatic shifts on ecological and cultural changes. Until recently, most explanations for prehistoric developments invoked anthropogenic causes, but the progressive development of paleoecological studies has incorporated a new perspective in which climate change and climate-human synergies have gained momentum. This paper reviews all paleoecological studies published to date and their contribution to a better understanding of Easter Island's prehistory, with a focus on four main aspects: (i) the discovery and settlement of the island, (ii) the eventual occurrence of climatic changes and its potential influence on landscape changes, (iii) spatiotemporal deforestation patterns, and (iv) the relationship between environmental, ecological and cultural shifts. Paleoecological research on Easter Island has proceeded through three main phases: a pioneer phase (1977–1992), a transitional phase (1993–2004) and a revival phase (2005–2020). During the pioneer and transitional phases, the paradigm of a self-induced prehistoric socioecological collapse known as the "ecocidal" hypothesis dominated the scene. However, new empirical evidence obtained during the revival phase highlighted the potential importance of climate change in prehistoric ecological and cultural developments. In addition, paleoecological records have provided novel insights into the initial discovery and occupation of Easter Island before Polynesian settlement. Paleoecological evidence has suggested or supported that (i) the island would have been discovered and sporadically/intermittently settled, possibly by Amerindian cultures, long before Polynesian colonization; (ii) climatic changes, especially centennial-scale droughts that occurred during the Medieval Climate Anomaly (MCA) and the Little Ice Age (LIA), would have influenced ecological trends and cultural developments; (iii) deforestation was not a synchronous island-wide process but occurred at different times and at different rates according to the catchment considered; and (iv) both climatic and anthropogenic drivers, along with feedbacks between them, would have been responsible for the prehistoric socioecological developments on Easter Island. A general conclusion is that Easter Island's prehistory is complex and cannot be resolved using simplistic and deterministic approaches from isolated disciplines. Rather, uncovering this prehistory requires an integrated framework with contributions from complementary research fields such as anthropology, archaeology, ethnography, history and paleoecology, among others. This paper explains the potential contributions of paleoecology, in the hope that researchers in other disciplines will be able to incorporate the available paleoecological knowledge into their own studies. From a paleoecological point of view, further coring is needed and the use of novel biomarkers is highly recommended. General recommendations are to increase the amount of raw data available in public repositories, to develop a multidisciplinary database for Easter Island and to adopt a problem-solving attitude focused on the main topics of interest. Highlights: A historical review of all published works on the paleoecology of Easter Island. Three historical phases: the pioneering phase, the intermediate phase and the revival phase. Emphasis on environmental changes and their potential influence on island's prehistory. Challenges the paradigm of an irreversible population/cultural collapse before European contact. Emphasizes the need for understanding the climate-ecology-culture system, its feedbacks and synergies.